An Artificial Intelligence (AI)–Based Counseling Service Application System for Distance Higher Education Students - Stefani Made Ayu Artharini Koesanto; Gunawan Wiradharma; Hudi Herdianto; Mario Aditya Prasetyo; Khaerul Anam (Jurnal Media dan Teknologi Pendidikan, 2025)
Distance higher education students face serious challenges in accessing counseling services due to the limited number of counselors, geographical barriers, and increasing academic workloads that affect mental health. At the same time, social stigma and time constraints discourage students from seeking direct help, creating a need for alternative technology-based solutions. This study aims to develop and validate KonselQ, an artificial intelligence (AI)–based counseling application designed to provide adaptive, responsive, and empathetic initial emotional support. The research employed a Research and Development (R&D) method using the Rapid Application Development (RAD) model, particularly focusing on the iterative user design stage. The main features of the application include an AI ChatBot based on Cognitive Behavioral Therapy (CBT), an AI Assistant offering mental health tips, psychoeducation, self-assessment tools, and a conversation history menu. The feasibility testing results showed an average rating of “very good” from experts: 87.5% for media, 82.6% for language, and 84.5% for psychological content. These findings demonstrate that KonselQ can serve as an inclusive, sensitive, and relevant digital counseling solution for students’ needs. This study highlights the potential of AI technology to expand access to counseling services, reduce psychosocial barriers, and support student mental well-being in the digital era.